Analisis Perbandingan Kinerja Keuangan Bank BNI Syariah Dan Bank BRI Syariah Di Masa Pandemi Covid-19 - Yulian Sahri; Andriansyah Bari; Ummi Kalsum; Randy Hidayat; Arraditya Permana (Politeknik Ganesha Medan, 2022)
Financial performance as a measuring tool to determine the process of implementing financial resources owned by the company. The Covid-19 pandemic had an impact on the banking sector, resulting in non-current financing due to debtor arrears as a result of many people losing their jobs and difficulties in paying financing. This study has the aim of conducting a comparative analysis of financial performance between BRI Syariah Banks and BNI Syariah Banks during the Covid-19 pandemic, using financial report notes for quarter 1, 2, 3 and 4 for 2019, quarter 1 for 2020 through independent testing. Sample T-Test. There is a difference between the financial performance of Bank BNI Syariah and Bank BRI Syariah from the aspect of ROA, NPF and BOPO, while from the aspect of CAR and ROE it shows that there is no significant difference between the financial performance of BRI Syariah Bank and BNI Syariah Bank. This paper recommends to BNI Syariah to pay attention to the ROE and NPF ratios, while to BRI Syariah Banks to pay attention to the CAR, ROA and BOPO ratios.